شبكة العلاقات الأسرية وتطلعات اللاجئين السوريين في الانتقال - Tobin, SA; Momani, F; Al-Yakoub, TA; AlMassad, RF (Refugee Studies Centre, University of Oxford, 2021)
تتناقض فكرة تطلعات اللاجئين السوريين إلى الانتقال مع الفكرةَ العامة القائلة بأن هؤلاء اللاجئين «العالقين» في النزوح هم ضحايا سلبيون لا فاعليةَ لهم. وبالمقابل، فحتى في حالة غياب خيارات الانتقال البدني القابلة للتطبيق الفعلي، يمكن أن يظل اللاجئون يمّنون أنفسهم بـ «المُضِي قُدُماً» حتى وإن لم يكونوا مستطيعين على ذلك بدنيا. Syrian refugees’ aspirations to move contradict the notion that those refugees who are ‘stuck’ in displacement are passive victims without agency. Rather, in the absence of viable options for physical mobility, refugees may still engage in aspirations to ‘move on’ even when they are not able to do so physically.